Unnecessary overtime as a component of time loss measures in assembly processes - Ebrahim, Zuhriah; Abdul Rasib, Amir Hamzah (Penerbit Universiti Teknikal Malaysia Melaka, 2017)
Hidden Time Loss (HTL) occurs along the production processes that have a significant effect on productivity. Overall Equipment Efficiency (OEE) is the most popular performance measurement tool used in the production line. Equipment performance is one of the measure components of OEE that caters HTL. However, OEE doesn’t really fit in measuring operation performance of assembly process especially the semi-auto assembly and the manual assembly process. There would be the amount of HTL have occurred along the semi-auto assembly and manual assembly processes that become critical when to involve high product variety at the same production line. Thus, the purpose of this paper is to introduce the Unnecessary Overtime (UOT) as one of the component of Time Loss Measures (TLM) in assembly processes. The structure of UOT is developed through a thorough literature study on manufacturing operations and its performance measures. The UOT structure is validated by using case study at five automotive manufacturing companies. The results show that the UOT is one of the components of TLM in semi-auto and manual assembly processes.